Turbulence in the Magnetospheres of the Outer Planets - Saur, Joachim (Frontiers in Astronomy and Space Sciences, 2021)
The magnetospheres of the outer planets exhibit turbulent phenomena in an environment which is qualitatively different compared to the solar wind or the interstellar medium. The key differences are the finite sizes of the magnetospheres limited by physical boundaries, the presence of a strong planetary background magnetic field and spatially very inhomogeneous plasma properties within the magnetospheres. These properties lead to turbulent fluctuations with amplitudes typically much smaller than the background field and to Alfv\'en times, which are often smaller than the non-linear interaction time scales. The magnetospheres of the outer planets are thus interesting laboratories of plasma turbulence. In Jupiter's and Saturn's magnetospheres, turbulence is well established thanks to the in-situ measurements by several spacecraft, in particular by the Galileo and Cassini orbiter. In contrast, the fluctuations in Uranus' and Neptune's magnetospheres are poorly understood due to the lack of sufficient data. Turbulence in the outer planets' magnetospheres have important effects on the systems as a whole. The dissipation of the turbulent fluctuations through wave-particle interaction is a significant heat source, which can explain the large magnetospheric plasma temperatures. temperatures. Similarly, turbulent wave fluctuations strongly contribute to the acceleration of particles responsible for the planet's auroras.